Ferulic acid inhibits ox-LDL-induced ferroptosis and apoptosis in RAW 264.7 cells via the HIF-1 signaling pathway - Wu, Xize; Pan, Xue; Kang, Jian; Huang, Yuxi; Ren, Jiaqi; Pan, Jiaxiang; Yu, Kaifeng; Li, Yue (Frontiers in Pharmacology, 2025)
ObjectiveFerulic acid (FA) has shown potential in treating atherosclerosis (AS) by improving lipid metabolism and exerting anti-hypoxic effects. This study aimed to validate the mechanism of FA in AS through in vitro experiments.MethodsNetwork analysis was employed to predict the mechanisms underlying the therapeutic effects of FA on AS. An in vitro foam cell model was established using RAW 264.7 cells treated with ox-LDL. Cellular lipid accumulation was detected using Oil Red O staining; cell viability was assessed by cell counting kit-8; mitochondrial morphology and function were evaluated by transmission electron microscopy and JC-1 staining; apoptosis levels were detected by TUNEL and DAPI staining; mitochondrial Fe2+ content was measured by Mito-FerroGreen; and Western blot was performed to determine the protein expression levels of HIF-1α, Bax, Bcl2, GPX4, and EGFR.ResultsNetwork analysis suggested that FA may exert its therapeutic effects on AS through the HIF-1 signaling pathway and is closely associated with the regulation of ferroptosis and apoptosis. FA upregulated the expression of ALOX5, BCL2, ERN1, GPX4, NOS3, and SLC2A1 mRNA and downregulated the expression of BAX, CYCS, EGFR, FLT1, HIF1A, NFKB1, NOS2, PARP1, and STAT3 mRNA. In vitro experiments demonstrated that FA reduces lipid accumulation, increases cell viability, improves mitochondrial function, and decreases reactive oxygen species content. Additionally, FA inhibited ferroptosis and apoptosis by suppressing the HIF-1 signaling pathway, up-regulating the expression of GPX4 and Bcl2, and down-regulating the expression of HIF-1α and Bax protein. HIF-1 agonists reversed these effects by activating the HIF-1 signaling pathway.ConclusionFA improves mitochondrial function and suppresses ferroptosis and apoptosis by inhibiting the HIF-1 signaling pathway, thereby treating AS.